Translating English Nominal Compounds Into Arabic - Kadhim, Kais Amir (2004)
This research is both a linguistic study and a search for the translation of English nominal compounds into Arabic. Compound constructions are very common in everyday speech and all types of written texts. They have been selected for study because Arabic translators often find difficulty in translating English nominal compounds into Arabic. The reasons for conducting such research are also linguistic and pedagogic in nature. Fresh-translators will find it difficult to cope with the complex constructions that are absent in Arabic. To determine this problems of dealing with complex constructions of this nature in translating from English into Arabic, Selkirk's theory and Vinay's and Darbelnet's methods are followed.